Code-Switching in Algerian English as a Foreign Language Speakers’ Facebook Interactions: Exploring Functions and Motives - Saida Tobbi (Turkish Academic Research Review)

(untitled)
This study examines code-switching among young Algerian English as a Foreign Language (EFL) Facebook users, with a focus on its functions and motivations. Code-switching, a widespread phenomenon in bilingual and multilingual societies, plays a significant role in shaping online communication practices in the digital era. Social media platforms like Facebook provide a dynamic environment where users seamlessly alternate between languages, reflecting their linguistic preferences, cultural identities, and communicative strategies. By investigating this phenomenon, the study seeks to shed light on the ways multilingual individuals navigate language choices in virtual spaces. The research was conducted with second-year English-major students at Batna 2 University, analyzing their Facebook interactions to uncover the purposes and underlying reasons for code-switching. A mixed-methods approach was adopted to provide both quantitative and qualitative insights. The primary dataset included 917 posts and comments collected from 42 students aged 19–22, who were selected through convenience sampling. These interactions were systematically analyzed to identify instances of code-switching, categorizing their specific linguistic and social functions. Additionally, semi-structured interviews were conducted with 17 randomly chosen participants from the same group. These interviews offered a deeper understanding of the participants' perspectives, adding qualitative depth to the analysis. The findings reveal that code-switching among these students is not a random occurrence but a deliberate and strategic choice. Several linguistic functions were observed, including the use of habitual expressions, filling lexical gaps, economizing words, clarifying meaning, and emphasizing specific points. From a social perspective, code-switching allowed participants to express affection, address specific audiences, and navigate cultural sensitivities, such as avoiding taboos. These diverse functions illustrate the adaptive ways in which students use their multilingual resources to enrich their communication and tailor their messages to their intended audiences. The motivations driving code-switching were equally varied and nuanced. Limited proficiency in English, coupled with linguistic constraints, often prompted students to switch to Arabic or French to ensure effective communication. Code-switching also served as a facilitative tool, enabling smoother interactions and fostering mutual understanding in a bilingual or multilingual online setting. Additional motivations included novelty-seeking, where alternating languages added stylistic diversity and creativity to their posts and comments. Emotional expression was another significant factor, as participants often turned to their native language to convey feelings more authentically. Politeness strategies also emerged as a key motivation, with students using code-switching to align with social norms, demonstrate respect, or address specific cultural expectations within their online communities. This study underscores code-switching as a purposeful and multifaceted linguistic strategy that transcends conventional norms to achieve communicative goals and enhance stylistic expression. The findings highlight the interplay between participants’ sociolinguistic contexts, linguistic competencies, and cultural identities, showcasing their adaptability to the demands of digital communication. By exploring the functions and motivations of code-switching in online environments, this research provides valuable insights into the evolving dynamics of language use in digital spaces. Future research could build on these findings by exploring code-switching practices on other social media platforms, investigating additional variables such as age, gender, or proficiency levels. Such studies would enhance understanding of the interplay between language, culture, and technology in digital communication.